The Bloomsbury Handbook of Japanese Religions - Baffelli, Erica (Bloomsbury Handbooks Ser., 2021)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Illustrations -- Acknowledgments -- Notes for the Reader -- Chapter 1 Introduction -- Chapter 2 Chaplaincy and Spiritual Care -- Chapter 3 Cultural Heritage -- Chapter 4 Disasters -- Chapter 5 Economy and Spirituality -- Chapter 6 Economy of Buddhism -- Case Study Buddhist Temples of the Future -- Chapter 7 Empire and Colonialism -- Case Study Aesthetics of Buddhist Modernism -- Chapter 8 Environmentalism -- Case Study Grassroots Environmental Activities in Risshō Kōseikai -- Chapter 9 Food Offerings -- Chapter 10 Folk Performing Arts -- Chapter 11 Gender -- Chapter 12 Globalization -- Case Study Diaspora Buddhism -- Chapter 13 Islam -- Chapter 14 Law -- Chapter 15 Materiality -- Chapter 16 Media and Technology -- Case Study World-Wide Shinto: The Globalization of "Japanese" Religion -- Chapter 17 Medicine -- Chapter 18 Minorities -- Case Study Daijō Islam (Mahayāna Islam) -- Chapter 19 "New Religions" -- Chapter 20 Pilgrimages and "Sacred" Geography -- Chapter 21 Politics -- Case Study Religion, Socialism, and Secularization -- Chapter 22 Premodern Traditions -- Chapter 23 Sexuality -- Chapter 24 Sound -- Case Study The Matsuri as Sonic Event -- Chapter 25 Space -- Chapter 26 Spiritualism and Occultism -- Chapter 27 Spirituality -- Chapter 28 Tourism -- Chapter 29 Women -- Case Study Mountain Worship and Women -- Bibliography -- Contributors -- Index.